Toward standardized exchange of plant 3D CAD models using ISO 15926. (February 2017) - Kim, Byung Chul; Jeon, Youngjun; Park, Sangjin; Teijgeler, Hans; Leal, David; Mun, Duhwan
Abstract: Plant three-dimensional (3D) computer-aided design (CAD) models typically consist of logical configuration, equipment specifications and ports, and 3D shapes. Because 3D CAD models are used as master information throughout a plant's entire lifecycle and many stakeholders are involved in such lifecycle, providing a method for sharing plant 3D CAD models among various stakeholders is very important. Standard 15926 from the International Organization for Standardization (ISO 15926) is a family of standards that is intended to support the sharing and integrating of all information during the life of a process plant. Therefore it is important for ISO 15926 to support plant 3D CAD models. In order to address this issue, this study investigates a standardized method to exchange plant 3D CAD models using ISO 15926. Information requirements regarding plant 3D CAD models are established, and then ISO 15926 reference data (classes, attributes, and templates) are extended to cover information requirements. For demonstration of the proposed method, we developed a prototype platform where plant 3D CAD models in ISO 15926 are loaded and retrieved. Highlights: We investigate a standardized method to exchange plant 3D CAD models using ISO 15926. Information requirements regarding plant 3D CAD models are established. ISO 15926 reference data are extended to cover the information requirements. For demonstration of the proposed method, we develop a prototype platform. Plant 3D CAD models in ISO 15926 are loaded and retrieved in the platform.